Roles of Nb on the oxidation characteristics and oxide scale evolution of Fe‐25Cr‐35Ni‐2.5Al‐XNb alloys at 1000°C and 1100°C. Issue 1 (1st September 2022) - Xu, Wanjian; Jia, Guodong; Pan, Jie; Wang, Zixie; Ouyang, Minghui; Xiao, Xueshan
Abstract: The oxidation characteristics of Fe‐25Cr‐35Ni‐2.5Al‐ X Nb (0, 0.6, and 1.2 wt%) alumina‐forming austenitic alloys at 1000°C and 1100°C in air were investigated. Results show that Nb has an important effect on the high‐temperature oxidation resistance. A bilayer oxide scale with a Cr2 O3 ‐rich outer layer and Al2 O3 ‐rich internal layer forms on the surface of the Nb‐free alloy and exhibits a poor oxidation resistance at 1000°C and 1100°C. With Nb addition, both the 0.6Nb‐addition and 1.2Nb‐addition alloys exhibit better oxidation resistance at 1000°C. Because of the third element effect, Nb addition reduces the critical Al content and forms a single external protective Al2 O3 scale, which greatly improves the oxidation resistance. After oxidation at 1100°C, niobium oxides (mainly Nb2 O5 ) are formed on the surface of the 1.2Nb‐addition alloy and destroy the integrity of the Al2 O3 scale, which causes the formation of Cr‐rich oxide nodules and eventually develops to be a loose bilayer oxide scale with NiCr2 O4, Cr2 O3, and Fe2 O3 outer layers and Al2 O3 inner layer. Abstract : This paper reports on the oxidation behavior of the Nb‐addition alumina‐forming austenitic (AFA) alloys at 1000°C and 1100°C in ambient air. The effects of Nb content and temperature on the oxidation resistance of AFA steel were investigated. Alloy with 0.6 wt% Nb‐addition has the best oxidation resistance. Particular attention was spent on the effect of Nb on the formation of the internal and external Al2 O3 film.